Manajemen Komunikasi Kepala Madrasah Dalam Meningkatkan Karakter Santri Di Pondok Pesantren Al-Fath Gebang - Nita Fitriani, Ahmad Zaki, Novita Sari (Pusdikra Publishing, 2023)
This study aims to find out how the communication management of the madrasah head improves the character of the students at the Al-Fath Gebang Islamic Boarding School, which includes communication between the head of the madrasa and students, teachers, staff, and all elements of the Islamic boarding school. Methodologically, this research is a qualitative research. Data was collected using in-depth interviews, observation and also documentation studies. After the data is collected, its validity is checked through validation standards, namely trust, transferability, dependence and firmness. The data analysis technique used is data reduction, presenting data, and giving conclusions from the research results. The findings in this study are: (1) In planning it focuses on the quality of graduates with good character who can master formal education and master education in Islamic boarding schools. This begins with careful planning based on the previous year's reflection, which is contained in the work program. MTs Principal Work Program. Al-Fath Gebang on the types of general activities, teaching, student affairs, manpower, infrastructure, administration, finance, and public relations. (2) Organizing the Madrasah Principal and being responsible to the Madrasah Principal in leading, planning, developing, directing, coordinating, supervising and controlling school activities in carrying out Public Relations programs in accordance with the vision, mission and work programs that have been set. (3) The implementation of this communication includes making Asma'ul husna signs, book study programs, sunnah prayers, tadars, and tahfizul Qur'an.